PENINGKATAN HASIL BELAJAR PESERTA DIDIK MELALUI MEDIA ULAR TANGGA PADA MATA PELAJARAN IPS KELAS VIII SMP NUSANTARA INDAH SINTANG - Pelipa, Emilia Dewiwati; Relita, Dessy Triana; Wulandari, Wulandari (STKIP Persada Khatulistiwa Sintang, 2024)
Â The purpose of this study was to describe the use of snakes and ladders learning media in improving student learning outcomes in social studies subjects in Class VIII of Nusantara Indah Sintang Junior High School in the 2023/2024 academic year. The method used in this research is qualitative research method. The subjects in this study were all students in class VIII of Nusantara Indah Junior High School Sintang in the 2023/2024 academic year, totalling 13 students, including 10 female students and 3 male students. The data collection techniques used were observation, interviews, documentation and test questions. Based on data analysis, the research results are as follows: (1) the application of snakes and ladders learning media is in accordance with the steps specified on the observation sheet. Judging from the results of teacher activity observations in cycle I was 90% and in cycle II was 100% with the assessment criteria for teacher activity observation results very well. (2) the improvement of students' learning outcomes can be seen from the test results, average scores, and classical completeness of each cycle. Where the average value of cycle I was 63.07 and the classical completeness was 53.84%, while the average value of cycle II was 88.46 and the classical completeness was 92.30%, meaning that snakes and ladders learning media can improve student learning outcomes. (3) Students' responses to the snakes and ladders learning media expressed positive responses based on statements on the students' interview sheets. It can be concluded that through snakes and ladders media can improve the learning outcomes of students in social studies class VIII SMP Nusantara Indah Sintang in the 2023/2024 academic year.Â Keywords: Learning Outcomes, Snakes and Ladders Learning MediaÂ